Sihung - Esa Hari Akbar (PANTUN, 2019)
The film production is entitled Sihung, a Sundanese word meaning in Indonesian siung, taring, caling (canine tooth, tusk). The term Sihung implies the violence in a pig fight, a folk game spreading in the culture of West Java people. The life of Ilma Nurjanah is represented through documentary film with direct cinema approach, a style whose approach focuses that the film maker and his camera will be accepted as part of the subject’s life. In fact, in certain cases the existence of the film maker and his camera is not realized anymore by the subject and her family. The film maker tries not to influence the daily life of his subjects through his existence The method applied in this study is analytical descriptive focusing in action research.Keywords: Sihung, pig fight, documentary film, direct cinema approach, Ilma Nurjanah